El papel de los gobiernos municipales en la gestion de los recursos naturales: villanueva: los recursos naturales en un municipio empobrecido - Mendoza, R.; Martínez, T. (Instituto de Investigacion y Desarrollo de la Universidad Centroamericana (NITLAPAN-UCA), Center for International Forestry Research (CIFOR), PROTIERRA-Iniform, 1999)
This is one of ten case studies of the role of municipal governments in forest related issues in the departments of Chinandega, Leon, and Rio San Juan in Nicaragua. It first characterizes the municipality, its agricultural production and mining, and the type of environmental problems it faces. Then it looks at the local institutions that exist and the projects that have been implemented there. Finally, it focuses specifically on the role of the municipal governments. Villanueva is a poor municipality that depends heavily on low productivity agriculture and mining. Fuelwood is more important than timber.